Information Seeking Behaviour of Elderly Persons in a Pandemic: Lessons from a Developing Country - Entsua-Mensah, Florence Odarkor; Ankrah, Ebenezer; Mensah Danquah, Monica; Commodore, Lenin Nii Korley (Ghana Library Journal, 2022)
Historically, pandemics have been notorious for their adverse effects on humans. One of the foremost steps in dealing with these adverse effects is timely access to adequate and reliable information on the pandemic. There is overwhelming evidence that ties information-seeking behaviour with access to relevant and timely information. Yet, there are sketchy studies on the information-seeking behaviour and access to relevant information on the COVID-19 pandemic. The situation is much more alarming when older persons, who are more susceptible to the virus are brought into perspective, especially those in developing countries. Undeniably, there is a significant gap between the health support systems in developing countries and that of developed countries. This creates a corresponding discrepancy between health information-seeking behaviour among these countries. This study examined the effect of the information-seeking behaviour of older persons on the confidence of surviving the pandemic in a developing country. The study adopted a quantitative approach. The purposive sampling technique was used to sample 100 respondents for the study. Descriptive statistics, Pearson’s Correlation and multiple regression were used to analyze the data. The findings of the study revealed that there is a significant relationship between older persons’ need for information and confidence in surviving the pandemic. The findings of the study also found that there is a significant relationship between an older person’s source of information and confidence in surviving the pandemic. In addition, the findings of the study showed that there is a significant relationship between older person’s information validation and confidence in surviving the pandemic. The study therefore recommended that there is a need for government and other related agencies to ensure that older people are equipped with the necessary information on the COVID-19 pandemic.